AI Technology in Technical Translation Courses - Zita Hajdu; János Farkas (Humán Innovációs Szemle, 2025)
This position paper examines the expanding role of machine translation and artificial intelligence in translation and translation training, highlighting both opportunities and limitations of using translation software and artificial intelligence that should be incorporated into university translation courses. Also, this paper provides a theoretical approach including new perspectives and personal viewpoints. The authors firmly believe there is a need for university translator-training programs incorporating AI literacy and featuring the importance of human linguistic, cultural, and contextual proficiency and machine-assisted translation tools. Literal translations, omissions, and incorrect or meaningless translations of terminology crucial in technical translation are the most frequent translation mistakes. The free versions of translation tools can only perform a limited number of tasks in a given time frame and have a limited vocabulary. Adaptation to different text styles is only achieved by the paid versions. After considering the lack of cultural background knowledge and other weaknesses, having a linguistically and technically competent translator to check the text is still essential. Ultimately, the paper follows a balanced approach that uses AI's benefits while highlighting the core competencies of human translators.